La clausura tridentina: protezione, separazione e interrelazione - Gabriella Zarri (Storia delle Donne)
The pair limes-clausura refers to the ancient Roman fortified frontier road which included defensive elements (cloister) along its route, thus allowing the limes to advance into enemy territory. The same pair must be kept in mind when considering the monastic enclosure – a place of protection and separation, but not of interruption of relations with the outside world. Historiography has investigated the meaning of the Tridentine enclosure in different directions, from time to time assuming as priorities the aspects concerning protection or those pertaining to separation. In this contribution I will highlight the elements that characterize the Tridentine enclosure and its consequences on monastic life, and also show the permeability of strict enclosure.